Transforming lives: biofortified beans reach 22.14 million people in Africa - Munthali, Justice; Rubyogo, Jean Claude (2024)
Nutrition-sensitive agriculture interventions were mainstreamed through the Pan-Africa Bean Research Alliance’s (PABRA) bean corridors approach between 2017 and 2023. These interventions have increased the number of women and men accessing and consuming biofortified high-iron beans (HIBs) and value-added bean products in Central, East, and Southern Africa from 720,000 to 22,14 million people. The continued adoption of HIBs and value-added bean products across 18 PABRA countries is attributed to complimentary projects that are promoting HIB release and mainstreaming through community outreach, school feeding programs, and value-addition and commercialization interventions.